Liability for Damage Caused by Loadshedding: A Consideration of Whether Collective Action for Redress by Consumers in South Africa is Possible - Tshepiso Scott-Ngoepe (Potchefstroom Electronic Law Journal)
The Consumer Protection Act 68 of 2008 (CPA) seeks to advance the social and economic welfare of consumers in South Africa by protecting vulnerable consumers, amongst other things. Loadshedding, which is characterised by a chronic shortage in the supply of electricity, was introduced into South African society in 2007 as a mechanism to distribute the demand for electricity. Its purpose is to relieve the stress on the national power grid when the demand is high to prevent a national blackout. One of the impacts of the power surge when electricity is restored to the power grid is damage to consumer property such as electrical appliances. In section 61 the CPA makes provision for consumers to institute an action for liability flowing from damage caused by “goods”. This paper argues that section 61 may be a good legal basis for collective redress by consumers in South Africa against power suppliers such as Eskom and the local municipalities.